Impact of early diagnosis, disease variant, and quality of care on the neurocognitive outcome in maple syrup urine disease: a meta-analysis - Scharré, Svenja; Mengler, Katharina; Schnabel-Besson, Elena; Kuseyri Hübschmann, Oya; Tuncel, Ali Tunç; Hoffmann, Georg F.; Garbade, Sven; Mütze, Ulrike; Kölker, Stefan (Genetics in medicine, 2025)
Purpose - Maple syrup urine disease (MSUD) is a rare inherited metabolic disease characterized by recurrent metabolic decompensations, neurocognitive impairment, and limited life expectancy. This meta-analysis aims to evaluate the impact of early diagnosis by newborn screening (NBS) on mortality and neurocognitive outcome in survivors, taking into account the quality of national health care systems. - Methods - Systematic literature search was performed according to Preferred Reporting Items for Systematic Review and Meta-Analysis protocol. Effects on outcome parameters were analyzed using meta-analytical measures and reanalysis of individual participant data. - Results - Thirty-three studies were included, reporting on 1141 individuals with MSUD. Participants with classic MSUD presented a more severe phenotype compared with variant MSUD as demonstrated by higher mortality rate (17.1% versus 0%), and lower median IQ (90 versus 104; P < .001, linear mixed model). NBS was associated with improved cognition (mean IQ: 95 versus 82; P = .014, random effects model) and decreased mortality (3% versus 14.6%; P = .028, Kaplan-Meier estimates) compared with individuals identified after onset of symptoms, in trend even after the exclusion of individuals with variant MSUD. Quality of national health care systems correlated with survival (P = .025, meta-regression) and permanent neurological symptoms (P = .031, meta-regression). - Conclusion - NBS is a prerequisite to improved outcome in individuals with MSUD; however, health benefit critically depends on the quality of the national health care systems.